2013
DOI: 10.1596/1813-9450-6724
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Solar Home Systems: An Analysis from Bangladesh

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 13 publications
(16 reference statements)
0
36
0
Order By: Relevance
“…It has positive effects on the enrolment and years of schooling of Indian girls (van de Walle et al 2015). In other studies by such results are confirmed for both boys and girls in India, Vietnam, Brazil, Peru (Khandker et al 2012(Khandker et al , 2013Lipscomb et al 2013;Arraiz and Calero, 2014). However no effects on enrolment, negative effects on attendance and school performance are found in other studies in India, Honduras and Uganda (Burlig and Preonas, 2016;Squires, 2015;Furukawa, 2014).…”
Section: Expenditure Schooling and Healthmentioning
confidence: 52%
See 2 more Smart Citations
“…It has positive effects on the enrolment and years of schooling of Indian girls (van de Walle et al 2015). In other studies by such results are confirmed for both boys and girls in India, Vietnam, Brazil, Peru (Khandker et al 2012(Khandker et al , 2013Lipscomb et al 2013;Arraiz and Calero, 2014). However no effects on enrolment, negative effects on attendance and school performance are found in other studies in India, Honduras and Uganda (Burlig and Preonas, 2016;Squires, 2015;Furukawa, 2014).…”
Section: Expenditure Schooling and Healthmentioning
confidence: 52%
“…Higher wages for women are found by Dasso and Fernandez (2015). Similarly, Khandker et al (2013) show significant increases in household incomes, via improvements in non-agricultural activities, but no effect on wages. Increases in non-agricultural income are also supported in studies by Dinkelman et al (2011), Lipscomb et al (2013 and Chakravorty et al (2016).…”
Section: Time Allocation and Labour Marketmentioning
confidence: 87%
See 1 more Smart Citation
“…Better quality, safer and healthier lighting for security, studying, social space, evening work (Komatsu et al 2011) (Mondal & Klein 2011;Samad et al 2013); and 2.…”
Section: The Transition To Solar Home Systems (Shs) For Lighting and Otmentioning
confidence: 99%
“…These small electricity access systems currently consist of a 20 to 100 Wp solar panel, a lead acid battery, a charge controller and basic loads. However, regardless of this success, there are certain limitations of this electrification option that includes-the poorest demographic segment cannot afford the solar home system [8]; there is explicit limitation to utilize the energy for productive purposes [9]; the systems often suffer from excess capacity as they are generally designed over-sized to assure high reliability, excess capacity is the generated energy that gets lost as the battery is full; the systems are not flexible regarding usage patterns and payment methods [10]. Therefore, to allow the off-grid population in Bangladesh to develop further economically, socially, and technologically, a better option for electrification need to be explored.…”
Section: Introductionmentioning
confidence: 99%